Asymmetric vinylogous Michael reaction of cyclic enones with silyloxy furans1. Issue 73 (21st September 2015) - Jadhav, Amol P.; Bhaskara Rao, V. U.; Singh, Pradeep; Gonnade, R. G.; Singh, Ravi P.
<x xml:space="preserve">Abstract</x> A chiral, primary diamine catalyzed enantioselective vinylogous Michael reaction of cyclohexenone/medium and large cyclic enones with various 2-silyloxyfuran has been explored.